2017
DOI: 10.1021/acscatal.7b02183
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Metal-Catalyzed Cycloisomerizations and Biocatalysis in Aqueous Media: Asymmetric Construction of Chiral Alcohols, Lactones, and γ-Hydroxy-Carbonyl Compounds

Abstract: The combination of the metal-catalyzed cycloisomerization of alkynes containing a tethered nucleophile as substituent in aqueous media (followed by the spontaneous hydrolysis, hydroalkoxylation, or aminolysis of the transiently formed five-membered heterocycles) with the subsequent enantioselective ketone bioreduction (mediated by KREDs) has been achieved. The overall transformations, which formally involve a three-step one-pot reaction, provide a variety of enantiopure valuable molecules (e.g., 1,4-diols, lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 86 publications
2
29
0
1
Order By: Relevance
“…Finally, a triple metal-/bio-/bio-catalyzed reaction was established by combining the aforementioned synthesis of chiral 1,4-pentandiol with a laccase/(2,2,6,6-Tetramethylpiperidin-1-yl)oxyl) TEMPO-catalyzed oxidation reaction giving rise to both antipodes of γ-valerolactone in quantitative yield and excellent enantiomeric excess [43]. combination of this subrogated hydration process with a concomitant bioreduction step promoted by KREDs allowed us to obtain the corresponding 1,4-pentanediol in good yields (up to 90%) and excellent enantiomeric excesses for both possible enantiomers after 24 h of reaction (Scheme 6) [29]. At this point, it is important to note that the reaction media coming from the metal-catalyzed reaction (containing the Pd(II)-Complex 6) was employed directly to feed the biocatalyst.…”
Section: Assembly Of Metal-catalyzed Cycloisomerization Of Allenyl Acmentioning
confidence: 97%
See 3 more Smart Citations
“…Finally, a triple metal-/bio-/bio-catalyzed reaction was established by combining the aforementioned synthesis of chiral 1,4-pentandiol with a laccase/(2,2,6,6-Tetramethylpiperidin-1-yl)oxyl) TEMPO-catalyzed oxidation reaction giving rise to both antipodes of γ-valerolactone in quantitative yield and excellent enantiomeric excess [43]. combination of this subrogated hydration process with a concomitant bioreduction step promoted by KREDs allowed us to obtain the corresponding 1,4-pentanediol in good yields (up to 90%) and excellent enantiomeric excesses for both possible enantiomers after 24 h of reaction (Scheme 6) [29]. At this point, it is important to note that the reaction media coming from the metal-catalyzed reaction (containing the Pd(II)-Complex 6) was employed directly to feed the biocatalyst.…”
Section: Assembly Of Metal-catalyzed Cycloisomerization Of Allenyl Acmentioning
confidence: 97%
“…Additionally, some kinetic experiments revealed that supramolecular Complex 5 had little effect on the studied enzymes, while free [AuCl(PMe 3 )] eroded the catalytic activity of the esterases or lipases. Inspired by these results and with the aim of expanding the synthetic scope of one-pot cascade processes involving metal-and bio-catalytic events in aqueous media, we turned our attention to the possible combination of the metal-catalyzed cycloisomerization of alkynes containing a tethered nucleophile (NuH; followed by the spontaneous hydrolysis of the transiently-formed five-membered heterocycles) with a concomitant bioreduction of the transiently-formed prochiral ketones without the need for any halfway isolation or purification steps (Scheme 5) [29].…”
Section: Assembly Of Metal-catalyzed Cycloisomerization Of Allenyl Acmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the combination of metal catalysis and biocatalysis has emerged in recent years as a powerful tool for developing new synthetic methodologies merging the advantages of both disciplines in terms of reaction scope and selectivity [64][65][66]. In this context, García-Álvarez, González-Sabín and co-workers described very recently the one-pot conversion of 4-pentynoic acid into enantiopure γ-hydroxyvaleric acid in aqueous medium, through the combined use of KAuCl4 and ketoreductases (KREDs) (Scheme 18) [67]. The process involves the initial gold-catalyzed cycloisomerization of the substrate, concomitant hydrolysis of the lactone to form levulinic acid, and final bioreduction of the keto group of the latter.…”
Section: Scheme 15 Catalytic Synthesis Of Phthalides From Terminal Amentioning
confidence: 99%